Evaluation of phosphorus removal from a lake by two drinking water treatment plants. Issue 7 (20th March 2020) - Huang, Yifeng; Mackenzie, Alec; Meteer, Laura; Hofmann, Ron
ABSTRACT: The impact of drinking water treatment plants on phosphorous in a lake has never been previously reported. In this mass balance study, phosphorus removal by a conventional plant and a membrane plant on Lake Simcoe was monitored. Approximately 16 kg of phosphorus per year were removed from the lake by the membrane plant, representing 72% of the influent phosphorous load to the plant. The membrane plant did not practice coagulation, so approximately two-thirds of the removal was via circulation of the treated water to the municipal wastewater treatment plant where phosphorous was removed. The remaining third was removed by the membranes. The conventional plant removed approximately 10 kg of phosphorus per year, representing 92% of the influent phosphorus loading. In this plant, polyaluminum chloride coagulation and subsequent sludge removal were responsible for approximately two-thirds of the phosphorous removal, with the remainder removed via circulation of the treated water to the municipal wastewater treatment plant. GRAPHICAL ABSTRACT: